Belajar Melalui Video di Media Sosial Dapat Meningkatkan Keterampilan Pemasangan Kateter pada Mahasiswa Keperawatan - Dahrizal Dahrizal; Gita Putri Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to analyze the use of video on social media as a learning medium for catheter placement skills in nursing students. The research design is a quasi-experimental design with pretest-posttest with group control. The results showed that there were differences in the average score of catheter placement skills in the intervention group before being given a video and 32.27 installation of a SOP catheter, after being given a video and SOP catheter placement being 72.73. Statistical test results of independent sample t-test obtained p value of 0,000 (p α α 0.05). Conclusion, there is an influence of the use of video on social media on catheter placement skills in nursing students. Keywords: Catheter, Learning Media, Video